2022
DOI: 10.1177/20499361221126868
|View full text |Cite
|
Sign up to set email alerts
|

Health care professional perspectives on discharging hospitalized patients with injection drug use-associated infections

Abstract: Background: Patients with injection drug use (IDU)-associated infections traditionally experience prolonged hospitalizations, which often result in negative experiences and bad outcomes. Harm reduction approaches that value patient autonomy and shared decision-making regarding outpatient treatment options may improve outcomes. We sought to identify health care professionals (HCPs) perspectives on the barriers to offering four different options to hospitalized people who use drugs (PWUD): long-term hospitalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…5 We reported in a previous study that most HCPs were supportive of providing patients with outpatient options, but still had concerns about selfdirected discharges, "non-traditional" antimicrobial treatment efficacy, and use of a PICC line to inject drugs. 15 In this study, patients and community partners emphasized patient autonomy and suggested that, while patients may not make the choice their care team prefers, taking this choice away can have negative short-and long-term consequences. Furthermore, patients demonstrate that they prioritize their health when they choose to remain in the hospital.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…5 We reported in a previous study that most HCPs were supportive of providing patients with outpatient options, but still had concerns about selfdirected discharges, "non-traditional" antimicrobial treatment efficacy, and use of a PICC line to inject drugs. 15 In this study, patients and community partners emphasized patient autonomy and suggested that, while patients may not make the choice their care team prefers, taking this choice away can have negative short-and long-term consequences. Furthermore, patients demonstrate that they prioritize their health when they choose to remain in the hospital.…”
Section: Discussionmentioning
confidence: 93%
“…10 Though many healthcare professionals (HCPs) are open to discussing these options with patients, there are some who are concerned that patients will not complete antibiotic courses after discharge, increasing the risk for antimicrobial resistance, infectious complications, and hospital readmission. 15 Shared decision making has been used with some success with PWID and may be useful in the context of treatment for IDU-associated infections, but studies on this topic specifically are limited. 16 Sikka et al 17 described an interprofessional provider conference to increase discharge options for patients with IDU-associated infections.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the effectiveness of in-hospital dissemination of harm reduction strategies, referrals to existing community-based services, and patient navigation at discharge [ 17 , 30 ]. While hospital providers are willing to present outpatient treatment options, many are not aware of existing community resources [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on earlier research conducted with health care professionals (HCPs), 9 patients, and community partners (Eckland et al personal communication, 31 January 2023), we developed a conversation guide ( Supplemental Appendix 1 ). We built on existing decision matrices and risk assessments developed by infectious diseases (ID) and palliative care experts, with real-time guidance and technical advice.…”
Section: Methodsmentioning
confidence: 99%
“… 8 In practice, many inpatient-based health care professionals recommend that people with IDU-associated infections remain hospitalized for prolonged periods because of the concern that they will inject drugs into indwelling central venous catheters, thereby risking another infection or death. 9 While prolonged hospitalizations might be justified to prevent self-harm, they may also infringe on patient autonomy. Patient autonomy is one of the central principles of medical ethics; 10 however, patients are often not given the ability to choose among medically feasible options which align with their values.…”
Section: Introductionmentioning
confidence: 99%